PERAN PUSTAKAWAN DAN MASALAH KECURANGAN AKADEMIK DI PERGURUAN TINGGI (Studi Kasus di Universitas Muhammadiyah Ponorogo) - Yolan Priatna (Maktabatuna, 2020)
Being a librarian is not an easy job. Especially in the information age like today. Various types of information manipulation are often carried out, even by academic people who uphold the value of honesty. This paper aims to provide information to the reader, that librarians have more role in the problem of information manipulation, especially regarding plagiarism that occurs in the academic environment (universities). The author uses the case study method that occurred at UPT. Muhammadiyah Ponorogo University Library. From this paper, it is known that the majority of students choose to consult with librarians to solve their plagiarism problems.